Teacher Perception of Using Posters in Teaching English Vocabulary to Slow Learners - Dian Fanny Sarahseti; Ernita Daulay (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Vocabulary is an important foundation in learning English, but it becomes a particular challenge for slow learner students who require a more structured visual approach and repetition. This study aims to explore teachers’ perceptions of the use of posters in teaching English vocabulary to slow learner students in an inclusive elementary school. A descriptive qualitative design was used with one third-grade English teacher as a participant selected purposively. Data were collected through non-participatory observation, semi-structured interviews, and documentation, then analyzed using thematic analysis by Braun and Clarke (2006). The results of the study found two main themes: first, the teacher has a positive perception of the effectiveness of posters in helping slow learner students understand vocabulary, increasing learning motivation, and strengthening memory through a poster rotation system every two to three weeks adjusted to the frequency of English learning once a week; second, the teacher faces challenges in limited time for media preparation and classroom management with students of different learning ability backgrounds. This study concludes that posters are a relevant medium and responsive to the learning needs of slow learner students, and the recommendations include the need for more adequate institutional support so that their implementation can run optimally and sustainably.